Proceedings of the International Conference on Bio-Inspired Systems and Signal Processing 2015
DOI: 10.5220/0005283403290337
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and Time Domain Parameters for The Classification of Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is the most common type of arrhythmia. This work presents a pattern analysis approach to automatically classify electrocardiographic (ECG) records as normal sinus rhythm or AF. Both spectral and time domain features were extracted and their discrimination capability was assessed individually and in combination. Spectral features were based on the wavelet decomposition of the signal and time parameters translated heart rate characteristics. The performance of three classifiers was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Our study achieved relatively consistent accuracy values in comparison with other similar studies. The study from Batista et al [12] reported the highest accuracy of 99.08% among the studies. However, the dataset described for validation was highly unbalanced between categories.…”
Section: Svm Classifier Vs 1d-cnn Algorithmmentioning
confidence: 90%
See 4 more Smart Citations
“…Our study achieved relatively consistent accuracy values in comparison with other similar studies. The study from Batista et al [12] reported the highest accuracy of 99.08% among the studies. However, the dataset described for validation was highly unbalanced between categories.…”
Section: Svm Classifier Vs 1d-cnn Algorithmmentioning
confidence: 90%
“…The following is a literature review of Machine Learning algorithms for the task of cardiac arrhythmia feature extraction and classification. ECG classification research can be divided into either heartbeat [11][12][13] or arrhythmia [5,10,12]. The most common algorithms included in studies are Support Vector Machine (SVM) [11][12][13][14], ANN [12], and CNN [10,[14][15][16].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations